Intraoperative MR Imaging Increases the Extent of Tumor Resection in Patients with High-Grade Gliomas - Knauth, Michael; Wirtz, Christian R.; Tronnier, Volker M.; Aras, Nurdagül; Kunze, Stefan; Sartor, Klaus (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: MR is being used increasingly as an intraoperative imaging technique. The purpose of this study was to test the hypothesis that intraoperative MR imaging increases the extent of tumor resection, thus improving surgical results in patients with high-grade gliomas.METHODS: Thirty-eight patients with intracranial high-grade gliomas underwent 41 operations. Using a neuronavigation system, tumors were resected in all patients to the point at which the neurosurgeon would have terminated the operation because he thought that all enhancing tumor had been removed. Intraoperative MR imaging (0.2 T) was performed, and surgery, if necessary and feasible, was continued. All patients underwent early postoperative MR imaging (1.5 T). By comparing the proportions of patients in whom complete resection of all enhancing tumor was shown by intraoperative and early postoperative MR imaging, respectively, the impact of intraoperative MR imaging on surgery was determined.RESULTS: Intraoperative MR imaging showed residual enhancing tumor in 22 cases (53.7%). In 15 patients (36.6%), no residual tumor was seen, whereas the results of the remaining four intraoperative MR examinations (9.7%) were inconclusive. In 17 of the 22 cases in which residual tumor was seen, surgery was continued. Early postoperative MR imaging showed residual tumor in eight patients (19.5%) and no residual tumor in 31 cases (75.6%); findings were uncertain in two patients (4.9%). The difference in the proportion of “complete removals” was statistically highly significant (P = .0004).CONCLUSION: Intraoperative MR imaging significantly increases the rate of complete tumor removal. The rate of complete removal of all enhancing tumor parts was only 36.6% when neuronavigation alone was used, which suggests the benefits of intraoperative imaging.